2015
DOI: 10.12968/ijpn.2015.21.4.179
|View full text |Cite
|
Sign up to set email alerts
|

Reported clinical outcomes of high-fidelity simulation versus classroom-based end-of-life care education

Abstract: Despite the fact that both strategies improved students' knowledge of EoLC, simulation-based EoLC education was perceived as better in terms of enhanced practical skills and improved emotional experience in their first clinical placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 27 publications
5
36
0
Order By: Relevance
“…Although there is no educational consensus whether simulation manikins should ‘die’ in undergraduate scenarios, there is evidence that senior medical students find this a useful learning experience 9. HFS improves end-of-life care learning for nursing undergraduates 10. There may be a perception that HFS is not useful in palliative medicine education since it is a less acute specialty.…”
Section: High-fidelity Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no educational consensus whether simulation manikins should ‘die’ in undergraduate scenarios, there is evidence that senior medical students find this a useful learning experience 9. HFS improves end-of-life care learning for nursing undergraduates 10. There may be a perception that HFS is not useful in palliative medicine education since it is a less acute specialty.…”
Section: High-fidelity Simulationmentioning
confidence: 99%
“…Fewer still appear to test the transferability of skills learnt in a simulated setting to real-life practice. Venkatasalu et al 10 found that HFS better prepared nursing students for their first healthcare placements both emotionally and in terms of ‘hands on’ skills. Rayment et al 12 demonstrated improved confidence in advance care planning by generalists using simulation with actors.…”
Section: Uses In Palliative Medicinementioning
confidence: 99%
“…Rasmansama Vekataslu, Kellher and Hua Shao [2015] found that nursing students preferred learning about end-of-life care in the simulation laboratory as opposed to the traditional classroom [7]. Simulation serves as a teaching-learning strategy that provides learners the ability to practice in a safe, realistic healthcare environment tending to the needs of a simulated patient [8].…”
Section: Simulation As a Driving Force For End-of-life Care Preparationmentioning
confidence: 99%
“…The use of simulation in healthcare has advanced beyond teaching medical knowledge and practising technical skills. Currently, it continues to expand into other aspects of non-technical medical education, including learning how to deal with death during infrequent events,1 practising end-of-life care2 and evaluating ethical standards 3. As healthcare educators find more novel ways to incorporate simulation to train practitioners, the need to address ethical considerations surrounding the use of high-fidelity simulation becomes more germane.…”
Section: Introductionmentioning
confidence: 99%